The Most Ancient “Puzzle Magazines”: Miscellanies of Intellectual Games from Ahiqar to Aristophanes (ENTHYMEMA, 2019)
Intellectual puzzles have a tendency to intermix and accumulate in miscellaneous collections, as happens in present-day puzzle magazines. This phenomenon may already be observed in old compilations (cf. Palatine Anthology, book 14, which draws on earlier sources) and theoretical treatises of antiquity (Clearchus’ On riddles, Athenaeus’ Deipnosophistaebook 10). Long before such works, fictional and legendary narratives provided a framework for stringing together multifarious types of mental games. The Near-Eastern Story of Ahiqarand the Greek Contest of Homer and Hesioduse the old theme of the competition between two great sages as a plot structure to accommodate a veritable anthology of genres of riddles. The Greek legend of Homer and Hesiod may have influenced Aristophanic comedies such as the Frogsand the Wasps. But while in the East the narrative form of the miscellaneous riddle contest was a fantastic outgrowth of the mixed compilations of wisdom literature, the corresponding Greek narratives were fictionalizations of the multifaceted entertainments of the symposion.
Keywords: Riddles; Riddle Contest; Narrative; Wisdom Literature; Symposion